2012
DOI: 10.2190/ag.74.4.d
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Generativity Model for Older Adults

Abstract: Generativity is a concept first introduced by Erik Erikson as a part of his psychosocial theory which outlines eight stages of development in the human life. Generativity versus stagnation is the main developmental concern of middle adulthood; however, generativity is also recognized as an important theme in the lives of older adults. Building on the work of Erikson, McAdams and de St. Aubin (1992) developed a model explaining the generative process. The aims of this article are: (a) to explore the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
0
25
0
4
Order By: Relevance
“…The act of exchanging social support may open up opportunities for communication (Ryan et al 1995), potentially increasing the fit between individuals and their social environment that allows older adults to feel accepted and motivated to engage in generative activities (Cheng 2009;Ehlman and Ligon 2012). Because previous research on FHH communication also showed the importance of social relationships (Koehly et al 2009), enhancing social relationships, especially the reciprocal social interactions, within families may play key roles in facilitating the FHH communication among older adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The act of exchanging social support may open up opportunities for communication (Ryan et al 1995), potentially increasing the fit between individuals and their social environment that allows older adults to feel accepted and motivated to engage in generative activities (Cheng 2009;Ehlman and Ligon 2012). Because previous research on FHH communication also showed the importance of social relationships (Koehly et al 2009), enhancing social relationships, especially the reciprocal social interactions, within families may play key roles in facilitating the FHH communication among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…FHH is a type of information older adults have that is very valuable to the health and well-being of their family members. In addition to the cultural factors discussed earlier, the low levels of FHH communication among older adults may also be due to not feeling that the information is being sought or valued by their family members, thus mitigating their motivation to share (Cheng 2009;Ehlman and Ligon 2012). Therefore, efforts to facilitate FHH dissemination within families should involve informing both older adults and their family members about the importance of collecting and sharing FHH information for the health of all family members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the United States Census Bureau (2012), 13% of the population was over the age of 65 in 2010, and it is projected that the number of older adults will double by 2030 (Centers for Disease Control and Prevention, 2012). Building on the strengths and generativity interests of older adults (Ehlman & Ligon, 2012), organizations have opportunities to advance their capacity to deliver and support intergenerational programs that, in turn, increase the capacities of the children they serve. As a result, this engagement can benefit both generations and their communities (Generations United, 2002;Gomperts, 2006;Kaplan, 1997).…”
Section: Introductionmentioning
confidence: 99%